Is GeneXpert MTB/RIF assay reliable for the diagnosis of pleural tuberculosis? - Muhammad Mudassir Shafiq, Muhammad Nadeem, Gul Afshan Zaidi, Naveed Arshad, Muzammil Khan, Zainab Niazi, Muhammad Mudassir Shafiq, Muhammad Nadeem, Gul Afshan Zaidi, Naveed Arshad, Muzammil Khan, Zainab Niazi (Journal of Rawalpindi Medical College, 2022)
Background: Tuberculosis is the most common cause of infectious diseases related mortality globally. Tuberculous pleural effusion is a common presentation of extra pulmonary tuberculosis and a diagnostic challenge most of time. The rapid diagnosis of tuberculous pleural effusion is essential for early treatment. GeneXpert is a new tool for rapid diagnosis but the ability to correctly diagnose of GeneXpert is a vital concern in the diagnosis of extra pulmonary tuberculosis. Objective: To determine the accurate ability of diagnosing the pleural fluid GeneXpert MTB/RIF assessment in the suspected pleural tuberculosis patients considering as gold standard to the pleural biopsy. Methods: This study was a validational cross sectional survey and it was conducted in pulmonology department of –removed for blind review---from 1st July to 31st December 2018 after approval of IRB. Participants with suspected pathology ≥ 18 year with exudative pleural effusion were included in the study. By implementing the process of standard technique, closed needle pleural biopsy was executed by means of ABRAM’S needle. The collected samples of patients were sent to the pathology department of Pakistan Institute of Medical Sciences for histopathology. Pleural fluid was referred to National Institute of Health Islamabad for GeneXpert MTB/RIF assessment on the alike day and reports were assembled. All findings were entered in a structured Proforma. Data was entered in SPSS version 20 and analyzed. Results: Total 180 patients were included; 65.6% patients were male. When the sensitivity of pleural fluid GeneXpert MTB/RIF examination was calculated it was 10.4% whereas, the calculated specificity was 72.8%. While +ve predictive value of GeneXpert was 22.2% and -ve predictive value was 52.1%. Likelihood ratio was 8.25 and ROC curve also showed similar values. Conclusion: The sensitivity of pleural fluid GeneXpert MTB/RIF assay is very low and specificity is moderate for diagnosis of pleural tuberculosis when compared with pleural biopsy. Key words: Extra pulmonary tuberculosis; GeneXpert; Pleural biopsy; Tuberculosis.